2017
DOI: 10.1093/mnras/stx1479
|View full text |Cite
|
Sign up to set email alerts
|

H i and cosmological constraints from intensity mapping, optical and CMB surveys

Abstract: We forecast constraints on neutral hydrogen (HI) and cosmological parameters using near-term intensity mapping surveys with instruments such as BINGO, MeerKAT, and the SKA, and Stage III and IV optical galaxy surveys. If foregrounds and systematic effects can be controlled -a problem which becomes much easier in cross-correlation -these surveys will provide exquisite measurements of the HI density and bias, as well as measurements of the growth of structure, the angular diameter distance, and the Hubble rate, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
91
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 75 publications
(91 citation statements)
references
References 74 publications
0
91
0
Order By: Relevance
“…We can therefore employ the Fisher matrix formalism [13] to forecast constraints on the HI abundance and bias along redshift. Using the aforementioned MeerKAT IM survey parameters, we find δ (Ω HI b HI )/(Ω HI b HI ) = 0.005 at z = 0.3 (L band) and [14]. These are more than one order of magnitude better than the currently available constraints from galaxy surveys, intensity mapping, and damped Lyman-α observations (see Table 2 in [15]).…”
Section: Hi Intensity Mapping With Meerkatmentioning
confidence: 78%
“…We can therefore employ the Fisher matrix formalism [13] to forecast constraints on the HI abundance and bias along redshift. Using the aforementioned MeerKAT IM survey parameters, we find δ (Ω HI b HI )/(Ω HI b HI ) = 0.005 at z = 0.3 (L band) and [14]. These are more than one order of magnitude better than the currently available constraints from galaxy surveys, intensity mapping, and damped Lyman-α observations (see Table 2 in [15]).…”
Section: Hi Intensity Mapping With Meerkatmentioning
confidence: 78%
“…The assumed sky overlap is 500 deg 2 with 500 hr MeerKAT time. The forecast constraint is δ (Ω HI b HI r)/(Ω HI b HI r) = 0.02 [10]. Figure 1, bottom left, shows the expected (angle-averaged) signal and errors for a DES-like photometric sample [13], with 4000 deg 2 sky overlap and 4000 hr MeerKAT time.…”
Section: Detecting the Hi Intensity Mapping Signal With Meerkatmentioning
confidence: 98%
“…Assuming a ΛCDM expansion history, the only unknown in the power spectrum is the HI density times the bias, Ω HI (z)b HI (z). Employing a Fisher matrix analysis, [10] has shown that the constraints on this quantity will be more than one order of magnitude better than current constraints from galaxy surveys, intensity mapping, and damped Lyman-α observations [11]. Detection can also be achieved by cross-correlating with optical surveys [8].…”
Section: Detecting the Hi Intensity Mapping Signal With Meerkatmentioning
confidence: 99%
See 1 more Smart Citation
“…Pourtsidou et al (2016) found that this last case considerably improves the 21 cm lensing detection prospects and excellent results can be achieved within frequencies observed by SKA-Mid and MeerKAT. In general, cross-correlating the galaxy and HI densities at postEoR redshifts can be particularly useful for constraining HI and cosmological parameters and alleviate issues arising from systematic effects that are relevant for one type of survey but not the other (Masui et al 2013;Wolz et al 2016Wolz et al , 2017Pourtsidou et al 2017). …”
Section: Multi-band Constraintsmentioning
confidence: 99%